Social Withdrawal (Hikikomori) Conditions in China: A Cross-Sectional Online Survey - Hu, Xinyue; Fan, Danhua; Shao, Yang (Frontiers in Psychology, 2022)
Objective: A form of pathological social withdrawal which is also called hikikomori has been proved its existence in China. But the prevalence and characteristics of hikikomori in China remain unknown. Past studies had investigated the hikikomori phenomenon in three cities of China. The purpose of this study is to discover the prevalence of hikikomori in a convenient online sample in China as well as the difference in demographic characteristics and other possible traits between hikikomori sufferers and the general population. Methods: A total of 1066 youths (mean age=22.85 years) in China completed the online questionnaire, which consisted of questions about demographics, the 25-item Hikikomori Questionnaire (HQ-25), the Internet Addiction Test (IAT), the Loneliness Scale (UCLA), and the General Health Questionnaire (GHQ). SPSS is used to evaluate the data. Results: Of the 1066 youths, 980 (91.9%) were identified as belonging to group A (be not social isolation nor withdrawn), 46 (4.3%) to group B (marked social isolation in one’s home or withdrawn with a duration of at least 3 months), and 40 (3.8%) to group C (marked both social isolation in one’s home and withdrawn with a duration of at least 3 months). The hikikomori group (combined group B and group C) accounted for 8.1 percent. The present data suggest that residence and loneliness are related to the occurrence of hikikomori. HQ-25 score of the hikikomori group was significantly higher than the comparison group. The UCLA score showed that those in the hikikomori group felt lonelier than those in the comparison. The regression model predicted hikikomori risk (2=38.658, P=0.000), the Hosmer-Lemeshow test value is 7.114 and P=0.524>0.05. Conclusion: The grouping criterion in our present study is reasonable and such a grouping criterion can screen out potential populations of hikikomori. When people develop into hikikomori sufferers in the present, their social withdrawal behaviors and feeling of loneliness are both much more severe than in the past. The possible relationships between hikikomori and loneliness reflect the need to give the youths more social support, to help them connect with society.